Cadaveric evaluation of first metatarsophalangeal joint preparation using a 2.0 mm MIS burr - Steven R. Cooperman, DPM, MBA, AACFAS; Lauren M. Christie, DPM, AACFAS; Chad A. Smith, DPM, AACFAS; Jacob M. Perkins, DPM, AACFAS; Vincent G. Vacketta, DPM, FACFAS; Roberto A. Brandão, DPM, FACFAS (Foot & Ankle Surgery: Techniques, Reports & Cases)
Minimally invasive techniques for foot and ankle procedures have gained popularity as an alternative to traditional open techniques, with proposed benefits including earlier weight-bearing, improved cosmesis, and decreased postoperative pain. The current study aimed to evaluate the efficacy of first metatarsophalangeal joint preparation using a minimally invasive burr while concurrently evaluating the risk of extensor hallucis longus tendon damage with this technique. Nine fresh, thawed cadaveric lower limbs were utilized for this investigation. A single, reproducible dorsomedial minimally invasive portal was created at the level of the first metatarsophalangeal joint, and a 2.0 mm burr was used to denude the cartilage for two minutes under fluoroscopic guidance. Digital calipers were used to measure the distance between the portal and the extensor hallucis longus tendon. The joints were then carefully disarticulated to evaluate the extent of cartilage debridement and surface area ratios were calculated. Results identified an average distance of 7.13 mm between the portal and the extensor tendon, with minor partial damage occurring to the tendon in 1/9 specimens. The proximal phalanx and metatarsal head ratios averaged 0.76 and 0.75, respectively, indicating approximately 76 % and 75 % of the respective joint surfaces were denuded. This study demonstrates comparable cartilage debridement to traditional open techniques based on historical data. Results of this study suggest that first metatarsophalangeal joint preparation can be effectively achieved with the use of a minimally invasive burr technique with fluoroscopic assistance, with a low risk of injury to the extensor hallucis longus tendon.